Comparison of Dual-Stack Dielectric Field Plates on β-Ga2O3 Schottky Rectifiers. (3rd May 2019) - Carey, Patrick H; Yang, Jiancheng; Ren, Fan; Sharma, Ribhu; Law, Mark; Pearton, Stephen J.
Abstract : The effects of bilayer field plates with various dielectric (SiO2 /SiNx, Al2 O3 / SiNx, HfO2 / SiNx ) on Ga2 O3 Schottky rectifier performance were investigated. The rectifiers were fabricated on 10 μm thick, Si doped (n = 2.8 × 10 16  cm −3 ) β-Ga2 O3 epitaxial layers grown by hydride vapor phase epitaxy on Ga2 O3 Sn-doped substrates (n = 4.8 × 10 18  cm −3 ) grown by edge-defined, film-fed growth. Temperature-dependent forward current-voltage characteristics were used to extract the average Schottky barrier height of 1.14 eV ± 0.03 eV for Ni, average ideality factor of 1.02 ± 0.02, and the Richardson's constant of 48.1 A/cm 2 K 2 . The reverse breakdown and leakage current were the two characteristics predominantly affected by the field plate dielectrics. The highest reverse breakdown reached was 730 V for rectifiers with Al2 O3 / SiNx, which was significantly higher than 562 V and 401 V for rectifiers with SiO2 / SiNx and HfO2 / SiNx, respectively. The on-resistance ranged from 3.8-5.0 × 10 −3 Ω-cm 2, which was dependent on diode size, with diameters from 50 to 200 μm. This led to a power figure-of-merit (VB 2 /RON ) of 140 MW-cm 2 . Design of the field plate is crucial in determining where reverse breakdown occurs.